2020
DOI: 10.1038/s41598-020-65861-w
|View full text |Cite
|
Sign up to set email alerts
|

Strong, tough and bio-degradable polymer-based 3D-ink for fused filament fabrication (FFF) using WS2 nanotubes

Abstract: WS 2 inorganic nanotubes (WS 2-NT) have been incorporated into Polylactic Acid (PLA) by melt mixing to create a biodegradable , mechanically reinforced nanocomposite filament. The filament was then processed by Fused Filament Fabrication (FFF) 3D-printer, and the morphology and characteristics before and after printing were compared. We found that addition of WS 2-NT to PLA by extrusion mixing increases the elastic modulus, yield strength and strain-at-failure by 20%, 23% and 35%, respectively. Moreover, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…WS 2 NTs are a promising choice of nanofiller because of their established synthesis methods [51,52], high aspect ratio, excellent mechanical properties [53], and lack of known cytotoxicity [54][55][56]. Moreover, recent studies on PLA/WS 2 NT nanocomposites blended by melt mixing showed the capacity of WS 2 NTs to easily disperse in the polymer matrix, promote PLA crystallization, and reinforce PLA at low loading (0.5 wt%) [57][58][59][60]. As an additional advantage, WS 2 could confer enhanced radiopacity to a PLLA-based BVS [61] due to the higher atomic number of tungsten (compared to the carbon and oxygen atoms of the PLLA), which would enable X-ray imaging of the BVS during implantation and follow-up treatment.…”
Section: Introductionmentioning
confidence: 99%
“…WS 2 NTs are a promising choice of nanofiller because of their established synthesis methods [51,52], high aspect ratio, excellent mechanical properties [53], and lack of known cytotoxicity [54][55][56]. Moreover, recent studies on PLA/WS 2 NT nanocomposites blended by melt mixing showed the capacity of WS 2 NTs to easily disperse in the polymer matrix, promote PLA crystallization, and reinforce PLA at low loading (0.5 wt%) [57][58][59][60]. As an additional advantage, WS 2 could confer enhanced radiopacity to a PLLA-based BVS [61] due to the higher atomic number of tungsten (compared to the carbon and oxygen atoms of the PLLA), which would enable X-ray imaging of the BVS during implantation and follow-up treatment.…”
Section: Introductionmentioning
confidence: 99%
“…WS 2 nanoparticles possess beneficial physical and mechanical properties [44,74] and have recently been studied for various biomedical applications such as friction-reducing agents in nickeltitanium alloys [75] and for reinforcing orthopedic implants [53]. The first step in the use of these nanomaterials for any medical application is to assess their biocompatibility in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that medical implants made of pure tungsten release tungsten into the blood stream as they corrode [34,35], studies on patients who received implanted tungsten embolization coils have revealed no toxicity in adult and pediatric patients [34,[36][37][38][39]. The literature lead us to the mineral tungstenite (tungsten disulfide, WS 2 ) for four reasons: methods to create high aspect ratio particles are well established (WS 2 nanotubes, WSNT) [40,41], WSNT disperse readily in PLA (among other polymers) without any surface modification [42,43], 0.5 wt% of WSNT increases the elastic modulus, yield strength and strain at failure of extruded PLA by 20%, 23% and 35%, respectively [44] and WS 2 nanoparticles show promising biocompatibility in vitro [45][46][47]. The high-aspect ratio (30-150 nm diameter, 1-20 ”m length, [44]) of WSNT is expected to favor preferential orientation along the hoopdirection of the BVS during tube expansion, the first step of BVS processing where a nearly radial deformation is applied to an extruded PLA tube.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of minute amounts of solvent adversely affected the nanotube-PLLA interaction and consequently the mechanical properties of the film. In the future, solvent-free processing of the film can be envisaged, like hot-pressing, or extrusion, and subsequent 3D printing [74].…”
Section: Discussionmentioning
confidence: 99%